Faktor yang Mempengaruhi Konsumsi Sayur dan Buah Mahasiswa Pendidikan Kesejahteraan Keluarga - Alda, Fahmia; Fridayati, Lucy; Elida, Elida (Journal of Home Economics and Tourism, 2016)
This study aimed to describe knowledge, attitude, individual experience, selection and food means and history of the disease PKK UNP. This type of research is quantitative descriptive with a population of 182 people, and a sample of 65 people. Sampling using proportional random sampling technique. Data collection techniques for the history of the disease, the individual experience, the selection and food means using open questionnaire (essay), while knowledge using closed questionnaire (multiple choice). Attitude measurement using a Likert scale. Furthermore, the data were analyzed descriptively. The results show the student's knowledge is quite good (47.69%), as well as attitudes fall into the category quite well (64.62%). Students like vegetables 92.3%. The most preferred type of vegetable is spinach (25.6%), while disliked is bitter melon (46.8%). Processed vegetable most preferred is the boiled vegetables (53.6%). All the students loved the fruit. The most preferred type of fruit is orange (18.2%), while unwelcome is durian and papaya (17.7%) in the form of processed fruit juice (50.00%). Digestive problems suffered were diarrhea (50.82%).Keywords: Consumption, Vegetable, Fruit